PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN SISTEM AGRIBISNIS KUBIS - Siska Prihantiwi; Totok Mardikanto; Agung Wibowo (Universitas Sebelas Maret, 2016)
This research aims to determine the causes of the role of educator, cabbage agribusiness system development, the role of educator, relationship roles extension with cabbage agribusiness development in Tawangmangu District, Karanganyar Regency. This research used a quantitative approach. The research location was selected Tawangmangu District, which has the highest production of cabbage in Karanganyar Regency. The data was used primary and secondary. Data analysis method was used partial correlation. The results of research showed agribusiness system development phase cabbage cultivation availability of production facilities and the very high criteria, harvest and post-harvest and marketing in the high criteria, institutional support in the low criteria. The role of agricultural extension as a motivator, mediator, supervisor and facilitator are in high criteria. The causes of extension role who are in the high criteria were the age and income of farmers, to the level of agricultural education and training in low criteria. Between roles as a motivator with a marketing instructor showed a significant relationship. Instructor's role as a mediator between the institutional supports showed a significant relationship. Between the role of agricultural extension as a supervisor and facilitator with cabbage agribusiness system development showed no significant relationship. Between the ages of farmers and role of instructor showed a significant relationship. The relationship between level of education, income and agricultural training, showed no significant association.